Sick youth. (Journal of Parents and Teachers, 2014)
When someone is sick, we care about him, we want him to heal and we look for the cause of the problem. Youth is said to be ill, but few people are relieved that, to a large extent, both cause and relief, are adults.
Keywords: Youth; disease; causes; help.